Semi-Crystalline Copolymer Hydrogels as Smart Drug Carriers: In Vitro Thermo-Responsive Naproxen Release Study - Snežana Ilić-Stojanović; Ljubiša Nikolić; Vesna Nikolić; Slobodan Petrović; Violeta Oro; Žarko Mitić; Stevo Najman (MDPI AG, 2021)
In this study, poly(N-isopropylacrylamide-co-2-hydroxypropyl methacrylate) hydrogels were synthesized using free radical initiated copolymerization method. Four hydrogels with different cross-linker concentrations were prepared. Semi-crystalline, cross-linked copolymer networks were confirmed by FTIR, SEM and XRD analysis. Variation of swelling behaviour was monitored gravimetrically and thermo-responsiveness has been noticed. An application of synthesized thermo-responsive hydrogels as carriers for the modulated release of anti-inflammatory model drug was investigated. Moreover, naproxen loading into these hydrogels was also determined using FTIR, SEM and XRD techniques and release was analyzed using HPLC method at simulated physiological conditions. Swelling kinetic and mechanism of water transport, as well as diffusion of naproxen through the hydrogels were analyzed. Thus, the aim of this work was to study various compositions of obtained hydrogels and their possibility of application as a thermo-responsive carrier for prolonged naproxen release in order to evaluate as a potential candidate for drug carrier in future pharmaceutical applications.